Effects of the Metal Ion on the Mechanism of Phosphodiester Hydrolysis Catalyzed by Metal-Cyclen Complexes - Hu, Qiaoyu; Jayasinghe-Arachchige, Vindi M.; Zuchniarz, Joshua; Prabhakar, Rajeev (Frontiers in Chemistry, 2019)
In this study, mechanisms of phosphodiester hydrolysis catalyzed by six di- and tetravalent metal-cyclen (M-C) complexes (Zn-C, Cu-C, Co-C, Ce-C, Zr-C and Ti-C) have been investigated using DFT calculations. The activities of these complexes were studied using three distinct mechanisms: (1) direct attack (DA), (2) catalyst-assisted (CA) and (3) water-assisted (WA). All divalent metal complexes (Zn-C, Cu-C and Co-C), coordinated to the BNPP substrate in a monodentate fashion and activated its scissile phosphoester bond. However, all tetravalent metal complexes (Ce-C, Zr-C and Ti-C) interacted with BNPP in a bidentate manner and strengthened this bond. The DA mechanism was energetically most feasible for all divalent M-C complexes, while the WA mechanism was favored by the tetravalent complexes, except Ce-C. The divalent complexes were found to be more reactive than their tetravalent counterparts. Zn-C catalyzed the hydrolysis with the lowest barrier among all M-C complexes, while Zr-C was the most reactive tetravalent complex. The activities of Ce-C and Zr-C, except Ti-C, were improved with an increase in the coordination number of the metal ion. The structural and mechanistic information provided in this study will be very helpful in the development of more efficient metal complexes for this critical reaction.